Shape memory textiles – technological background and possible applications - Guido Ehrmann; Andrea Ehrmann (Communications in Development and Assembling of Textile Products, 2021)
While shape memory alloys (SMAs) and shape memory polymers (SMPs) can already be found in diverse applications, shape memory textiles are less often used. Nevertheless, they are regularly investigated. Typical ways to produce shape memory textiles (SMTs) are introducing shape memory wires, printing shape memory polymers on them (“4D printing”), or using textile materials such as poly(lactic acid) (PLA) which show shape memory properties on their own. This review gives a brief overview of these technological possibilities and possible applications of shape memory textiles.